Sport participation, screen time, and personality trait development during childhood - Allen, Mark (My University, 2015)
This investigation explored the contribution of extracurricular sport and screen time viewing (television viewing and electronic gaming) to personality trait stability and change during childhood. Two independent samples of 3,956 young children (age 6) and 3,862 older children (age 10) were taken from the Longitudinal Study of Australian Children. Parent-reported child sport participation, screen time, and personality traits were measured at baseline and again 24 months later. Young children who were more active recorded more of a decrease in introversion, less of a decrease in persistence, and less of an increase in reactivity, than those who were less active. Older children who were more active recorded less of an increase in introversion and more of an increase in persistence than those who were less active. In addition, young children who continued participation in extracurricular sport had greater intra-individual stability of personality for introversion. These finding suggest that an active lifestyle might help to facilitate desirable personality trait stability and change during childhood.
Keywords: Child Development; Child Development -- Physical; Childhood and child development; Child Development; Physical; Childhood and child development